SISTEM INFORMASI SIMPAN PINJAM BERBASIS WEBSITE KOPERASI “RikRik Gemi” SMKN 15 BANDUNG - Yudi Ramdhani; Rein Lantin (Jurnal Informatika, 2016)
Abstract KPRI public vocational secondary schools 15 of Bandung "Rikrik Gemi" is one of the cooperatives engaged in savings and loans, with financial management that still use conventional system with using books and Microsoft Excel. This method is less effective due to savings and loan transactions that occur higher so the calculation is also growing. Especially with many members who apply for a loan, where it takes a long time to validate loan application process. The Methods of information system design savings and loans are made using waterfall methodology and use two UML diagram consisting of use case diagrams and activity diagrams. Implementation and manufacture of web-based systems with structured programming techniques using the programming language PHP and MySQL database. This information systems saving based website could provide an alternative rapid and accurate in data access savings and loans to facilitate and assist performance management and also to improve the performance of the current system to be computerized well. Keywords: Information System, Loan and Save Cooperative, PHP and MySQL